Change in facial shape in two cohorts of Japanese adult female students twenty years apart - Hossain, M.G.; Saw, A.; Ohtsuki, F.; Lestrel, P.E.; Kamarul, Tunku (Singapore Medical Association, 2011)
Introduction: Secular changes in the head and body dimensions of the Japanese population were recorded during the last century, but studies on Japanese adult facial shape were poorly documented. This study aimed to document the secular changes in facial shape and their association with craniofacial measures of Japanese adult female students. Methods: Data were collected from 1998-2001 and 1975-1979 from institutions in Tokyo and Kyoto. The prosopic index (PI) was derived from morphological facial height (n-gn) and bizygomatic breadth (zy-zy). Multiple regression analysis was used to determine the association between PI (facial form) and craniofacial measures. Results: Larger mean values for morphological facial height (n-gn) and for PI, but smaller values for bizygomatic breadth (zy-zy) and bigonial breadth (go-go) were observed in the current sample compared to their predecessors 21 years ago. The most prevalent facial shapes were mesoprosopic (30.53 percent) and euryprosopic (45.14 percent) for the current and previous series, respectively. There was a significant positive relationship between the PI and head length (g-op) (p less than 0.01), head breadth (eu-eu) (p less than 0.01) and head height (v-po) (p less than 0.05), and a negative relationship between the PI and head circumference (g-g) (p less than 0.01) and minimum frontal breadth (ft-ft) (p less than 0.01). Conclusion: Our results suggest that a narrowing of facial shape has been occurring for approximately 21 years in adult Japanese females. The best predictor variables for PI were head length, head circumference, head breadth, minimum frontal breadth and head height.